Management of an Organization’s Development PotentialBased on a Balanced Scorecard - L. F. Shilova; A. N. Bystrova; D. L. Skipin; A. S. Gurina; K. A. Kostina (Учёт. Анализ. Аудит)
The article considers the issues of managing an Organization’s Development Potential based using a Balanced Scorecard. When innovative technological processes are implemented one of the most effective mechanisms of strategic management is a balanced scorecard. The use of this tool leads to successful development of the organization and increases its value. The core feature of the balanced scorecard is development potential. The authors define what “development potential” is and propose the methods for its analysis. To assess the development potential the following indicators can be used: work satisfaction, staff stability, labor capacity, etc. The authors propose a methodology for analysis of development potential by polling to find differences in the quality of WORKING LIFE in different categories of employees. The polling was carried out among the employees of Oil and Gas Company. The sample covered 342 people: 31% of which belong to whitecollars (managerial staff) and 69% were blue-collars. The questions in the questionnaire were divided into 9 sections, which evaluate various aspects of quality of WORKING LIFE: assessment of working results, workers’ participation in management, assessment of professional knowledge and skills, skill level, the impact of work on personal lives of employees and others. For each question average weighted arithmetical mean is calculated in order to obtain numerical data. To find deviations the authors correlate the obtained numerical values with the normal level of average weighted arithmetic. The result of this research is the proposal about transition to the balanced scorecard, which, in its conceptual framework, in the authors’ view, focuses on the development potential of the whole team. Management of development potential is based on the interaction between the organization and the employee, the use of the balanced scorecard can make this interaction more effective.